Penerapan Prinsip ISO 31000 dalam Pengelolaan Risiko Strategis: Studi Kasus pada Kegagalan Transformasi Bisnis Kodak - Anantha Nisrina Zahirrah; Ibnu Alif Ifanialdy; Nasywa Nahdah Raniah; Alvianus Kristian Sumual (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study analyzes the failure of Kodak’s business transformation by examining the company’s inability to implement the principles of ISO 31000 in managing strategic risks. Using a qualitative case study approach, the research highlights how Kodak underestimated digital disruption and failed to conduct comprehensive risk identification, objective analysis, and forward-looking risk evaluation. As a result, Kodak’s responses to digital innovation were reactive and fragmented, causing the company to lose competitiveness and ultimately file for bankruptcy in 2012. A comparative analysis with Fujifilm is presented to demonstrate how effective risk management can transform threats into strategic opportunities. Unlike Kodak, Fujifilm applied proactive risk identification, executed aggressive diversification, and restructured its organization to adapt to long-term technological shifts. These actions reflect the core principles of ISO 31000, particularly in integrating risk management into organizational decision-making and risk treatment. The study concludes that strategic risk management based on ISO 31000 is essential for companies facing technological disruption. Kodak’s failure and Fujifilm’s success highlight the importance of disciplined, structured, and adaptive risk management to ensure long-term business sustainability